Prarancangan Pabrik Akrolein Dari Gliserol Menggunakan Dengan Desain Alat Utama Evaporator Gliserol (EV-101) Pada Proses Reaksi Dehidrasi Gliserol - Jayanti Mandasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Acrolein (2-propenal / C3H4O / CH2 = CHCHO)) is the simplest unsaturated aldehyde compound. The main characteristic of acrolein is its high reactivity due to the conjugation of the carbonyl group with the vinyl group. The uses of acrolein include protecting liquid fuels from microorganisms, making the essential amino acid methionine and as a good separatorand dispersing agent, widely used in the ceramic, paper and electroplating industries. Currently acrolein is produced commercially mainly using the propylene oxidation method. However, producing acrolein with glycerol as raw material is more promising in terms of cost and renewability. The effective utilization of the glycerol by-product from biodiesel production can reduce the cost of biodiesel production and thereby increase the developmentof the biodiesel industry. The main design tool is the evaporator (EV-101) which serves to concentrate glycerol to a purity of 98% as a raw material in the acrolein manufacturing process. This design is carried out in several steps, namely collecting data sources to support the establishment of the factory, calculating the mass and energy balance, calculating the network of heat and mass exchangers as well as analyzing and designing the glycerol evaporator and supporting accessories. The operating conditions for evaporator 101 (EV-101) are with a feed temperature of 107.7 ℃ and a pressure of 1 bar and a steam temperature of 200 ℃. The type of evaporator used is the Long Tube Vertical Evaporator.Keywords: Acrolein, biodiesel, energy balance, evaporator, glycerol.